2018
DOI: 10.1111/anu.12863
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variation in the dietary ratio of linseed oil to fish oil on growth, body composition, tissues fatty acid composition, flesh nutritional value and immune indices in Manchurian trout,Brachymystax lenok

Abstract: In order to study the effects of linseed oil substitution on the growth, body composition, tissue fatty acid composition, flesh nutritional value and immune indices of juvenile Manchurian trout, five feed types containing different levels of linseed oil (LO) mixed with fish oil (FO) were prepared: 0 (0 LO); 250 g/kg (25 LO); 500 g/kg (50 LO); 750 g/kg (75 LO); and 1000 g/kg (100 LO); and fed to juvenile Manchurian trout (initial weight 6.43 ± 0.02 g) for 9 weeks. The results showed that substitution of FO with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…The growth performance of fish has been reported previously 31 . Briefly, both the final weight (22.33 ± 0.35 g, mean ± SE) and weight gain for the LO100 diet were significantly lower than for the other diets ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The growth performance of fish has been reported previously 31 . Briefly, both the final weight (22.33 ± 0.35 g, mean ± SE) and weight gain for the LO100 diet were significantly lower than for the other diets ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of C18 PUFA (LNA + LA) was kept constant in the diets (approximately 55% of the total fatty acid). The diets were made according to method of Yu et al (2019). Briefly, all raw materials were crushed and fully mixed according to the principle of gradual expansion, and then, linseed oil, corn oil and palm oil were fully mixed and added to the dry ingredients.…”
Section: Experimental Dietsmentioning
confidence: 99%
“…The Manchurian trout ( Brachymystax lenok ) is a cold‐water fish distributed in northern China with high economic value. At present, there have been several studies looking at its nutritional physiology (Chang, Niu, Jia, Li, & Xu, 2017; Liu, Gao, Cao, Yin, & Liu, 2018; Yu et al., 2019). Previous experiments showed that VO (which is rich in C18 PUFA) can partly or completely replace FO without affecting the growth and immunity of fish (Liu et al., 2018; Yu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the nutritional quality indexes of fillet lipids were calculated according to the formulas below (Dagtekin et al, 2017; Garaffo et al 2011; Kocatepe et al 2019; Yu et al 2018). IndexofAntherogenicity(IA)=[(4C14:0)+C16:0+C18:0]/(MUFA+n -0.333333em6PUFA+n -0.333333em3PUFA)IndexofThrombogenicity(IT)=(C14:0+C16:0+C18:0)/(0.5MUFA+0.5n -0.333333em6PUFA+3n -0.333333em3PUFA)+(n -0.333333em3PUFA/n -0.333333em6PUFA)FleshLipidQuality(FLQ)=(C20:5n3+C22:6n3/totalFA)hypocholesterolaemic/Hypercholesterolaemic(h/H)=(C18:ln9+…”
Section: Methodsmentioning
confidence: 99%